Investigate the Effectiveness of Plants Grown Alongside the Roads of Baqubah City for Phytoremediation of Nickel: Testing the efficiency of some plants grown on the roadsides in Baqubah city as a phytoremediation of nickel - Shakir, Sura; Hamza Rathi, Munther (ASJ - Academic Science Journal, 2025)
Heavy metals are classified as non-degradable contaminants, which are considered to be among the most harmful to the environment. Samples for the research were obtained in September (2022). In this research, the ability of five species of plants grown on roadsides in the city of Baqubah - Diyala province to remove nickel from the environment (soil, air and water) was tested.The study aimed to evaluate the responsibility of various plants grown along The roadside in nickel bioremediation by estimating the concentration of nickel in the plants' leaves and soil, as well as computing the Bioaccumulation Factor (BAF).The plants used in the study were: Nerium oleander, Eucalyptus camalduulensis, Albizia lebbeck, Ficus nitida, and Callistemon viminalis species from three different locations in Baqubah city were: the industrial area, Hospital street and Al-Mustafa neighborhood. The results indicated substantial variances across the different plant types. It also showed that the soil is not polluted with nickel, compared with the natural abundance of the element in the Baqubah city, and the global average for uncontaminated soil.The C. viminalis plant was better for phytoremediation in all regions than other plants, while the other plants varied in their ability to phytoremediation of nickel. All study areas were uncontaminated to moderately contaminate with nickel and located in Class1 of Igeo classification.